Adolescent and Adult Children of Parents with Parkinson's Disease: Incorporating Their Needs in Clinical Guidelines - Morley, David (SAGE-Hindawi Access to Research, 2011)
Purpose. To compare the quality of life (QoL) and emotional well-being of the offspring of parents with Parkinson's disease (PD) and multiple sclerosis (MS) and to consider results in light of current UK clinical guidelines. Methods. 143 adolescent and adult children of parents with PD and MS were postally administered the Parental Illness Impact Scale and a measure of emotional well-being. Results. Minimal differences were observed between the two groups in both QoL and emotional well-being. Levels of mild to moderate depression were substantially greater than those of the general population. Conclusions. The nonsignificant differences reported indicate a similar degree of impact across the two conditions assessed. A significant body of evidence demonstrates the considerable impact of parental MS, with the needs of children being acknowledged in current clinical guidelines. There is a need to similarly acknowledge the potential impact of parental Parkinson's in UK guidelines for PD.